Fatores genéticos e de meio na idade ao primeiro parto de caprinos leiteiros - Gonçalves, Heraldo Cesar [UNESP]; De Almeida E Silva, Martinho; Regazzi, Adair José; Lopes, Paulo Sávio; Martins, Elias Nunes; Ramos, Alcides Amorim [UNESP] (My University, 1997)
Data on age at first kidding (IPP) were collected on seven farms in the Brazilian Southeastern region which explored Parda Alpina, Saanen and Toggenburg breds. Least squares (LS) were used to evaluate the effects of environmental factors and to estimate variance components, and the derivative-free restricted maximum likelihood (DFREML) method was used to estimate the variance components of IPP and to genetically evaluate the goats used in the southest region of Brazil. The LS mean and standard error of IPP were 607.18 ± 17.09 days. The interaction of year x kidding season had a significantly influenced IPP, indicating that management conditions varied among the seasons within each specific year, with a direct influence on body weight which is the main criterion adopted by farmers to decide when the animal is ready to breed. The effect of farm-breed combination influenced the IPP. The compararison among levels of farm-breed were done by cluster analysis. The results indicated that the individual goat management within each farm had a greater influence than breed, since goats of different breeds showed high and similar values on those farms having a high mean IPP. Heritability estimates obtained by LS using intraclass correlations among paternal half-sibs and those obtained by REML were 0.220 and 0.369, respectively.
Genetic and environmental factors on the age of first kidding of milk goats
Keywords: Goats; Heritability; Reproduction